ANALYSIS OF THEORETICAL AND METHODOLOGICAL APPROACHES TO ASSESSING ENTERPRISE ECONOMIC SECURITY AT VARIOUS LEVELS OF ECONOMIC MANAGEMENT IN CONTEMPORARY CONDITIONS - Любохинець, Лариса; Вінскевич, Олександр (SWorldJournal, 2026)
Assessing the economic security of an enterprise in contemporary conditions is a complex, multidimensional process encompassing a hierarchical spectrum from global trends to the individual characteristics of the entity. This approach enables the transform